2019 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2019
DOI: 10.1109/iros40897.2019.8967823
|View full text |Cite
|
Sign up to set email alerts
|

Look Further to Recognize Better: Learning Shared Topics and Category-Specific Dictionaries for Open-Ended 3D Object Recognition

Abstract: Service robots are expected to operate effectively in human-centric environments for long periods of time. In such realistic scenarios, fine-grained object categorization is as important as basic-level object categorization. We tackle this problem by proposing an open-ended object recognition approach which concurrently learns both the object categories and the local features for encoding objects. In this work, each object is represented using a set of general latent visual topics and category-specific diction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Results showed that the proposed system supports classical learning from a batch of labelled training data and open-ended learning from online experiences of a robot. In the continuation of this work, we would like to to study how to use LDA approaches in finegrained object recognition scenarios [54] and investigate the possibility of overcoming the mentioned limitations to use deep learning approaches in open-ended domains [55].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the proposed system supports classical learning from a batch of labelled training data and open-ended learning from online experiences of a robot. In the continuation of this work, we would like to to study how to use LDA approaches in finegrained object recognition scenarios [54] and investigate the possibility of overcoming the mentioned limitations to use deep learning approaches in open-ended domains [55].…”
Section: Discussionmentioning
confidence: 99%
“…Such categories could for example be different items of cutlery, different dog, cat or other pet breeds, a variety of box shaped objects (like food container boxes, tissues, a stack of paper, etc) or different writing utensils. Attempts have been made to tackle this issue by introducing fine grained object recognition [50,83,215]. Finegrained object recognition takes into consideration small visual details of the categories that are important to distinguish them from similar categories.…”
Section: Fine-grained Object Recognitionmentioning
confidence: 99%
“…Kasaei et al [94] proposed an open-ended object category learning approach just by learning specific topics per category. In another work [83], an approach is proposed to learn a set of general topics for basic-level categorization, and a category-specific dictionary for fine-grained categorization (Fig. 8).…”
Section: Fine-grained Object Recognitionmentioning
confidence: 99%